Analisis perbandingan performansi mesin pengkondisian udara dengan kompresor terisolasi dan tidak terisolasi - Rasta, I Made; Susila, I Dewa Made (Jurnal Energi Dan Manufaktur, 2012)
During installation of an AC Split, the technician usually didn’t release the compressor insulation. They assumed that the compressor will have longer life time rather than without insulation. Actually, in this case the compressor worked hardly in insulated condition by glass wool. The overload signal then will immediately stop the electric current to the compressor. The research was aimed to investigate the AC performance if compressor in insulated condition and without insulation. The tested unit was AC 2 PK, water chiller type. The result showed, COP decreased 0.35; electrical consumption increased 18.7 Watt; and the refrigerating effect slightly decreased, respectively.
Keywords: Performance, energy consumption, compressor